Influência do gesso agrícola no desenvolvimento da soja CV. BRS Tracajá - Silva, Marcelo Ribeiro da (2018)
The application of surface agricultural gypsum can increase the base saturation in the subsoil and reduce the effect toxic effect of Al3+ and decrease its influence on root growth in the soil layers, allowing improvements in the vegetative components of soybean yield. In this context, the objective was to evaluate the influence of doses of gypsum in the development of soybean cv. BRS Tracajá in a greenhouse. The experimental design was completely randomized, with six replicates, three replicates collected at 45 days after planting (DAP) for the vegetative components of the aerial part and components of the dry matter, being the other 110 DAP for the variables productivity components. Treatments consisted of agricultural gypsum doses: 0, 3, 6, 9, 12 Mg ha-1 were randomized in plot. For the variables of the root components, the plot of subdivided plots in the same experimental model of aerial part and treatments were followed, and the comparisons of the doses of gypsum were given within layers 0-0,20; 0,20-0,40 and 0,40-0,60 m, with three replicates. The experimental unit consisted of a PVC vessel 150 mm in diameter and 600 mm high with a plant. There was influence of the gypsum in the vegetative components of the aerial part of the soybean, in the number of leaves, stem diameter, chlorophyll a and total chlorophyll, except for shoot height, chlorophyll b, stomatal CO2 conductance and foliar temperature. Increasing doses of gypsum influenced positively the components of the fresh and dry matter of the shoot and root. The root components presented a positive response as a function of the increasing doses of gypsum in the layers 0-0.20 and 0.20-0.40 m, except in the layer of 0.40-0.60 m. For the root components as a function of the layers, a positive response was also observed within the gypsum doses, except the root length in the layer of 0.40-0.60 m at doses 6 to 12 Mg ha-1. The productivity components presented the maximum technical efficiency in the dose of agricultural gypsum 6 Mg ha-1, with the exception of the mass of 100 grains in the dose 12 Mg ha-1.